Impact of the COVID-19 pandemic on the incidence of healthcare-associated Clostridioides difficile infection in a tertiary healthcare facility in the Republic of Ireland - Saied Ali; Sinead McDermott (Elsevier, 2023)
Summary: Background: Clostridioides difficile is the foremost cause of nosocomial infectious diarrhoea and one of the most prevalent healthcare associated infections (HAIs). Aims: To investigate the impact of the coronavirus disease 2019 (COVID-19) pandemic on the incidence of healthcare associated C. difficile infection (HA-CDI). Methods: A retrospective study was conducted from January 2019-December 2022 inclusive at a tertiary University Hospital in Dublin, Ireland. The study period was divided into COVID-19 and non-COVID-19 periods determined in tangent with the then national incidences of COVID-19 and number of hospitalized patients with COVID-19. Analyses looked at quantity of testing performed, incidence rates and antimicrobial consumption. An independent samples t-test was used to determine significance between groups. Results: Between COVID-19 and non-COVID-19 periods, no statistically significant difference was observed among HA-CDI rates per 10,000 bed-days (2.1 cases vs 1.76 cases; P=0.34), consumption of defined daily doses per 100 bed-days of antimicrobials - all antimicrobials (83.36 vs 89.5; P=0.091), fluoroquinolones only (3.71 vs 4.46; P=0.067), third-generation cephalosporins only (4.17 vs 4.43; P=0.449), carbapenems only (3.28 vs 3.26; P=0.944) - or the number of C. difficile tests performed per 10,000 bed-days (321.81 tests vs 326.63 tests; P=0.696). Conclusions: There was no difference in the incidence rates of HA-CDI between COVID-19 and non-COVID-19 periods at our institution.